Acinar Cell Carcinoma of the Pancreas: A Literature Review and Update - Chaudhary, Poras (Indian J Surg, 2014)
Pancreatic acinar cell carcinoma is a rare tumour, accounting for only about 1 % of all pancreatic tumours. The long-term survival for patients with acinar cell carcinoma is significantly better than the long-term survival of patients with pancreatic adenocarcinoma. As no large series of patients with acinar cell carcinomas exist, our understanding of this disease comes mainly from small case series and case reports. Aggressive surgical resection with negative margins is associated with long-term survival in these more favourable pancreatic cancers. There are no clear treatment guidelines for patients in whom complete surgical resection with curative intent is not possible. Acinar cell carcinomas are chemoresponsive to agents that have activity against pancreatic adenocarcinomas and colorectal carcinomas because of the shared genetic alterations between these cancers. The role of neoadjuvant or adjuvant chemoradiotherapy remains unproven. The aim of this article is to present current knowledge on acinar cell carcinoma and comprehensive review of available literature.